Antimicrobial Resistance Profile of Staphylococcus aureus from Clinical Samples of Patients Visiting Sushma Koirala Memorial Hospital - Karki, Rajan; Chandi, Dhruba Hari; Pant, Shyam Prasad (International Journal of Innovative Research in Medical Science, 2017)
Staphylococcus aureus is commonly isolated pathogen from clinical specimen with increasing trend of antimicrobial resistance. The aim of the study was to isolate S. aureus from the pus and wound swabs and determine their susceptibility pattern. This study was carried out in Sushma Koirala Memorial Hospital (SKM), Kathmandu, from June 15, 2013 to May 30, 2014, following the standard microbiological protocol. Out of 285 samples (pus and wound swabs), S. aureus was isolated from 65 (22.80%), of which 38 (58.46%) from male and 27 (41.53 %) from female. Fourteen (21.53%) isolates were identified as MRSA and remaining 51 (78.47%) were Methicillin-Susceptible (MSSA). Among MSSA isolates, all isolates were 100 % susceptible to Amikacin, Tetracycline and Vancomycin. The susceptibility to Ciprofloxacin, Erythromycin and Penicillin was 52.94%, 68.63%, and 10.20% respectively. Among MRSA isolates, no resistance was seen to Amikacin, Chloramphenicol, Tetracycline, and Vancomycin but only 66.67 % of isolates were susceptible to Clindamycin. To remaining all antibiotics tested, Cefotaxime, Cephalexin, Ciprofloxacin, Erythromycin, Gentamicin and Penicillin, the susceptibility was lower than the 37%. In this study, all the MRSA isolates were multidrug resistant (MDR), whereas 25.49 % of MSSA isolates were MDR. Six (9.2 %) of the total isolates were obtained as Penicillinase producing S. aureus by penicillin disk zone-edge method.